Influence of Entrepreneurial Network Ecosystem on Growth of Leather Manufacturing Small and Medium Enterprises in Kenya - Kunusia, Lilian; Namusonge, Gregory; Naikuru, Susan (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: The purpose of this study is to examine how entrepreneurial network ecosystem affect growth of leather manufacturing small and medium enterprises in Kenya. Methodology: A purposeful sample was used to select respondents. Questionnaires designed to examine the views of the entrepreneur about SME networking were distributed amongst SMEs in leather manufacturing. The research instrument was based on a five-point Likert scale. The questionnaire administered contained 2parts, Part 1: contains general information, while Part 2: contains specific questions relating to networking. Findings: The results of the analysis showed a generally positive overview of SME networking in Kenya. The respondents agreed that networking is of great benefit to their businesses. Unique Contribution to Theory, Practice and Policy: Relevant bodies such as Kenya association of manufacturing (KAM), ministry of livestock, Kenya association of tanners should come up with framework to ensure there relevant and coordinated network ecosystem in the leather manufacturing in Kenya.